Major Issues in Business Process Management: Key Concerns presented in Academy from a Brazilian Perspective - Confort, Valdemar; Santoro, Flávia (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2015.5881, 2015)
This paper is part of a major research in Business Process Management (BPM). There are international publications that identify the evolution of this area and practical challenges in several perspectives. This paper contributes with a comprehensive survey that identifies, from a Brazilian perspective, the evolution of the academic interest and the practical challenges of the national organizations. The expected results are, first, that this work can provide evidences to answer our research question: What are the issues BPM in Brazil? In addition, we expect to contribute with an approach and instruments that can be applied in the future in a new evaluation, following the same process of this research. This first part presents the results of a key concerns classification of all the papers presented in a Brazilian´s Conference: the Workshop of Business Process Management. With this first part, we aim to contribute by showing and discussing what are the academy keys concern and compare it with the BPM International Conference.